Biodegradação de diesel no solo por consórcio microbiano bioestimulado com soro de leite - Silva, Daniela da (2020)
Petroleum and its derivatives, when mismanaged, can cause several problems to the environment and an example is the contamination of the soil by hydrocarbons. Bioremediation is a technique that can be used in the treatment of this pollutant, as it is a technology with great potential and that can be applied using bio-enhancement and biostimulation. Whey is an ally in this type of technique due to its high nutritional value that aids in biodegradation and on the other hand it is a reuse option for this waste which, if improperly disposed of, also causes environmental mpacts on both soil and water. In this work, bioremediation was combined with biostimulation through whey, in order to create a biostimulated microbial consortium. Hermetically sealed glass flasks were used and the soil with no history of contamination was added together with diesel in different concentrations of [2%] and [10%]. Sodium alginate capsules containing microbial pools in different concentrations of diesel were created in order to compare these factors and an analysis was carried out to verify the emulsification potential of these microorganisms in environments contaminated by BTEX. The statistical analysis of this test was carried out by applying a factorial experiment with two factors: the treatments and the levels that are the concentrations of diesel in [2%] and [10%] and with [5%] of significance. However, for respirometry, no statistically significant results were found, since the treatments obtained cumulative values of the titration averages, very close. Consortia without biostimulation with whey showed a better performance in respirometric analysis when compared to the biostimulated consortium. The analysis of emulsification of these microorganisms showed great growth potential in diesel, since the whey consortium presented [63.51%] of emulsifying index, followed by the ISB 45 bacterium with [56.58%] and ISB 42 with [45,57]. These are promising results that show that these isolates, when present in a stressful environment, stand out for having the ability to degrade these hydrocarbons.